Teknik pengajaran kemahiran bertutur Bahasa Arab di SMKA di Malaysia - Mohd Ala-Uddin, Othman; Zawawi, Ismail; Ab Halim, Tamuri; Nik Mohd Rahimi, Nik Yusoff (2011)
Speaking is one of the important components in any language curriculum. It is an aspect that determines success in second and foreign language teaching and learning processes and as a benchmark for mastering any language. This is an exploratory research aims at identifying the techniques which teachers normally used in teaching the spoken Arabic language in National Religious Secondary Schools (NRSS) in Malaysia based on their own perceptions and also their students' perceptions. In addition, it also aims to discover whether the techniques support the communicative approach which is the central focus in Arabic Language Curriculum (ALC) in Malaysia . Two sets of questionnaires were used as the instruments in this study which comprised NRSS teachers who implemented ALC and students from NRSS based on four zones. The findings illustrate that teachers exert more technical instructions which required short and direct responses such as question and answer, and listen and repeat techniques whereas the techniques less executed by teachers are replacement, conversion, ripple and expansion techniques. It also includes exercises which necessitate students to simply recognize whether a statement is true or false, advanced exercises, and also getting students to perform role-plays and compose couplet essays. The techniques that used short and direct responses by the teachers limit students' opportunities to communicate. This is because having the opportunities is one of the important aspects for the learners in using the language for communication. This findings show that the teaching of Arabic language in Malaysia do not support communicative approach in ALC.